2023
DOI: 10.3390/ijms24108945
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between COVID-19 and Coagulopathy: Pathophysiological and Clinical Evidence

Abstract: Since the first description of COVID-19 infection, among clinical manifestations of the disease, including fever, dyspnea, cough, and fatigue, it was observed a high incidence of thromboembolic events potentially evolving towards acute respiratory distress syndrome (ARDS) and COVID-19-associated-coagulopathy (CAC). The hypercoagulation state is based on an interaction between thrombosis and inflammation. The so-called CAC represents a key aspect in the genesis of organ damage from SARS-CoV-2. The prothrombotic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 165 publications
1
7
0
1
Order By: Relevance
“…Some important markers of these events are interleukin (IL)-6, C-reactive protein (CRP), platelet (Plt), and leukocyte (WBC) count. 20 In the present study, we found an increase of IL- 2D).…”
Section: Hpse and Mmps Levels In The Serum Of Covid-19 And Non-covid-...supporting
confidence: 63%
“…Some important markers of these events are interleukin (IL)-6, C-reactive protein (CRP), platelet (Plt), and leukocyte (WBC) count. 20 In the present study, we found an increase of IL- 2D).…”
Section: Hpse and Mmps Levels In The Serum Of Covid-19 And Non-covid-...supporting
confidence: 63%
“…A dysregulated immune response is typified by altered transcriptional patterns and heightened inflammatory markers, and it can last up to six months. Myeloid-derived suppressor cells and cytotoxic CD4+ T-cells are two characteristics of severe COVID-19 that are still present in PASC [ 119 ]. In addition to their ability to facilitate viral coinfections and be associated with persistent symptoms, chronic inflammation, and monocyte activation can contribute to immunopathology.…”
Section: Implications Of Altered Molecular Processes In Long Covid Sy...mentioning
confidence: 99%
“…A Itália foi um dos países mais afetados no início da propagação desta infecção. A doença causada por este vírus foi denominada Doença do Coronavírus 2019 , que ainda representa um desafio crítico para a comunidade de saúde mundial, apesar da redução da mortalidade após a campanha global de vacinação (Ragnoli et al, 2023).…”
Section: Introductionunclassified